2012
DOI: 10.1371/journal.pone.0046531
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Set of Sex Pheromones Identified in the Cuttlefish Sepia officinalis

Abstract: BackgroundThe cephalopod mollusk Sepia officinalis can be considered as a relevant model for studying reproduction strategies associated to seasonal migrations. Using transcriptomic and peptidomic approaches, we aim to identify peptide sex pheromones that are thought to induce the aggregation of mature cuttlefish in their egg-laying areas.ResultsTo facilitate the identification of sex pheromones, 576 5′-expressed sequence tags (ESTs) were sequenced from a single cDNA library generated from accessory sex glands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…seaweeds, to form the egg mass. The successive ovulation, oocyte transport, encapsulation and fertilization steps are orchestrated by neuropeptides (Henry et al, 2013(Henry et al, , 1999(Henry et al, , 1997, ovarian regulatory peptides (Bernay et al, 2006, 2004, Zatylny et al, 2000a, 2000b, and sex pheromones (Enault et al, 2012). Although neuropeptides are not the only regulators involved in regulation of egg-laying mechanisms, they nevertheless play an important role in integrating environmental parameters such as the photoperiod, temperature, salinity or depth.…”
Section: Introductionmentioning
confidence: 99%
“…seaweeds, to form the egg mass. The successive ovulation, oocyte transport, encapsulation and fertilization steps are orchestrated by neuropeptides (Henry et al, 2013(Henry et al, , 1999(Henry et al, , 1997, ovarian regulatory peptides (Bernay et al, 2006, 2004, Zatylny et al, 2000a, 2000b, and sex pheromones (Enault et al, 2012). Although neuropeptides are not the only regulators involved in regulation of egg-laying mechanisms, they nevertheless play an important role in integrating environmental parameters such as the photoperiod, temperature, salinity or depth.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical communication probably plays an important role in these mechanisms. Boal and collaborators demonstrated that crude ovary and female accessory sex gland (ASG) extracts had an attracting power during behavioral tests, while Enault and collaborators recently characterized waterborne sex pheromones. In the squid Loligo pealeii , the occurrence of a β-microseminoprotein-like pheromone inducing extreme aggression in males was demonstrated in the egg mass .…”
Section: Introductionmentioning
confidence: 99%
“…Using a transcriptomic approach, Enault and collaborators [9] discovered a third category of regulatory peptides, namely the sex pheromones expressed and released by the oviduct gland, and cleaved from three protein precursors into bioactive peptides ranging between 1.3 and 8 kDa.…”
Section: Egg-laying: Regulationmentioning
confidence: 99%
“…In Sepia officinalis, Enault and collaborators [9] identified three major related transcripts encoding secreted peptides and expressed in the oviduct gland. RT-PCR and mass spectrometry analyses revealed that transcripts and expression products were co-localized in the oviduct gland.…”
Section: Sex Pheromonesmentioning
confidence: 99%
See 1 more Smart Citation